The SMC5/6 Complex Subunit NSE4A Is Involved in DNA Damage Repair and Seed Development - Díaz, Mariana; Pečinková, Petra; Nowicka, Anna; Baroux, Célia; Sakamoto, Takuya; Gandha, Priscilla Yuliani; Jeřábková, Hana; Matsunaga, Sachihiro; Grossniklaus, Ueli; Pecinka, Ales (The Plant cell, 2019)
The maintenance of genome integrity over cell divisions is critical for plant development and the correct transmission of genetic information to the progeny. A key factor involved in this process is the STRUCTURAL MAINTENANCE OF CHROMOSOME5 (SMC5) and SMC6 (SMC5/6) complex, related to the cohesin and condensin complexes that control sister chromatid alignment and chromosome condensation, respectively. Here, we characterize NON-SMC ELEMENT4 (NSE4) paralogs of the SMC5/6 complex in Arabidopsis (Arabidopsis thaliana). NSE4A is expressed in meristems and accumulates during DNA damage repair. Partial loss-of-function nse4a mutants are viable but hypersensitive to DNA damage induced by zebularine. In addition, nse4a mutants produce abnormal seeds, with noncellularized endosperm and embryos that maximally develop to the heart or torpedo stage. This phenotype resembles the defects in cohesin and condensin mutants and suggests a role for all three SMC complexes in differentiation during seed development. By contrast, NSE4B is expressed in only a few cell types, and loss-of-function mutants do not have any obvious abnormal phenotype. In summary, our study shows that the NSE4A subunit of the SMC5-SMC6 complex is essential for DNA damage repair in somatic tissues and plays a role in plant reproduction.
Keywords: oprava DNA; Transcriptome; Arabidopsis Proteins; Protein Binding; DNA Repair; DNA Damage; proteiny buněčného cyklu; Arabidopsis; Cell Cycle Proteins; duplikace genu; regulace genové exprese u rostlin; Gene Expression Regulation, Developmental; podjednotky proteinů; Genome, Plant; Up-Regulation; upregulace; proteiny huseníčku; Protein Subunits; poškození DNA; vazba proteinů; transkriptom; Gene Duplication; Gene Expression Regulation, Plant; Ovule; Seeds; semena rostlinná; pyl; genom rostlinný; Pollen; vajíčko rostlin; vývojová regulace genové exprese